Progesterone attenuates depressive behavior of younger and older adult C57/BL6, wildtype, and progesterone receptor knockout mice - Frye, Cheryl A. (Pharmacology, biochemistry and behavior, 2011)
Progesterone may have actions independent of intracellular progestin receptors (PRs) to influence depressive behavior. To investigate this, we examined effects of progesterone (P; 10mg/kg, SC) on the depressive behavior of mice in the forced swim test (FST). In Experiment 1, subjects were 4 to 6months old, intact or ovariectomized (OVX) female and intact or gonadectomized (GDX) male, C57/BL6 mice. Progesterone reduced depressive behavior of young diestrous and OVX mice but male mice were impervious to effects of P. In Experiment 2, subjects were intact aged (20–28months old) C57/BL6 female and male mice. Progesterone reduced depressive behavior of aged female and male C57/BL6 mice, albeit effects were greater among males. In Experiment 3, effects of P were examined in 4 to 6months old, gonadally-intact, female and male mice that were wildtype or PR knockouts (PRKOs). Progesterone decreased depressive behavior of young adult, wildtype and PRKO mice, which showed greater immobility than did their wildtype counterparts. In Experiment 4, subjects were 18–24months old wildtype or PRKO mice (Exp 4). Progesterone decreased immobility among wildtype and PRKO mice (which were not different in terms of their baseline depressive behavior). Together these data demonstrate that P decreases depressive behavior of young and older adult C57/BL6, wildtype and PRKO mice, which suggest that acute anti-depressant effects of P may occur independent of actions at “classic” PRs. ► Progesterone had anti-depressant effects for young adult female but not male mice. ► These sex differences were attenuated in aged 15 mice. ► Progesterone had antidepressant effects among progestin receptor null mutants.